Additive association of knowledge and awareness on control of hypertension: a cross-sectional survey in rural India. Issue 1 (January 2021) - Ragavan, Rathina Srinivasa; Joshi, Rohina; Evans, Roger G.; Riddell, Michaela A.; Thankappan, Kavumpurathu R.; Chow, Clara K.; Oldenburg, Brian; Mahal, Ajay S.; Kalyanram, Kartik; Kartik, Kamakshi; Suresh, Oduru; Thomas, Nihal; et al.
Abstract : Objective: To determine whether there is an interaction between knowledge about hypertension and awareness of hypertension on the treatment and control of hypertension in three regions of South India at different stages of epidemiological transition (see Video, Supplemental Digital Content 1, http://links.lww.com/HJH/B426 ). Methods: Using a cross-sectional design, we randomly selected villages within each of rural Trivandrum, West Godavari, and Chittoor. Sampling was stratified by age group and sex. We measured blood pressure and administered a questionnaire to determine knowledge and awareness of hypertension. Logistic regression was used to assess associations of awareness and knowledge about hypertension with its treatment and control in participants with hypertension, while examining for statistical interaction. Results: Among a total of 11 657 participants (50% male; median age 45 years), 3455 had hypertension. In analyses adjusted for age and sex, both knowledge score [adjusted odds ratio (aOR) 1.14 [95% confidence interval (CI) 1.12--1.17)] and awareness [aOR 104 (95% CI 82--134)] were associated with treatment for hypertension. Similarly, both knowledge score [aOR 1.10; 95% CI (1.08--1.12)] and awareness [aOR 13.4; 95% CI (10.7--16.7)], were positively associated with control of blood pressure in those with hypertension, independent of age and sex. There was an interaction between knowledge and awareness on both treatment and control of hypertension ( P of attributable proportion <0.001 for each). Conclusion: Health education to improve knowledge about hypertension and screening programs to improve awareness of hypertension may act in an additive fashion to improve management of hypertension in rural Indian populations. Abstract : Supplemental Digital Content is available in the text